Analysis of energy and greenhouse gas balance as indexes for environmental assessment of wheat and maize farming: a case study - Móslem SAMI; Mohammad Javad SHIEKHDAVOODI; Morteza ALMASSI (Acta Agriculturae Slovenica)
In this study, the net balance of greenhouse gas (GHG) emission and energy of wheat and maize production systems in two farms in Khuzestan province of Iran was assessed. The results showed that totally wheat farming is more efficient than maize farming in terms of energy and CO2-eq indexes. The total energy requirement for maize and wheat farming was 92560.24 MJ ha-1 and 39624.15 MJ ha-1, which caused the emission of 20191.47 and 7541.04 kg CO2-equivalent per hectare in maize and wheat farms respectively. Electricity, fertilizers and fuel were the most important pollutants of environment in terms of energy and gas emission in both farms. Theses inputs consumed 55.52, 22.62 and 6.44 % of total energy of maize and 47.32, 21.19 and 9.01 % of total energy of wheat farm and were responsible for the 88.60, 8.79 and 2.03 % of CO2-equivalent in maize and 86.54, 9.54 and 3.24 % of CO2-equivalent in wheat farms respectively. The results of this study also showed that the enhancement of 60.74 and 27.02 % in energy ratio and 46.06 and 27.87 % in CO2-eq index in maize and wheat farming can be expected using simple improving scenarios.